(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Hepatocellular carcinoma (HCC) or Liver cancer is a common type of tumor mainly found in patients that are diagnosed with cirrhosis. Our recent therapies for liver cancer include laser treatment, surgery, or standard medicines like sorafenib, Lenvatinib has major side effects like bleeding gums, blurred vision etc. so to prevent these types of side effect and make a more bio- familiar drug with body environment tried to make the peptide-based drug. Casein kinase 2 and Toll-like receptor 2 are selected as the target of our study, which are essential for cell growth and proliferation and act as a potent suppressor of apoptosis, offering an important link to their involvement in cancer, as deregulation of both cell proliferation and apoptosis belong among the key features of cancer cell biology. Various vital amino acids, of smaller-chain dipeptides were selected. The Swiss ADME tool was used to predict the pharmacokinetic properties of dipeptides such as GIT absorption, Lipinski, etc. and then they were subjected to Pro-tox II software to predict the toxicity. The Swiss online tool DOCK & CB dock-2 (PDB code: 4GRB) was used for docking, along with Chimera visualizer and Discovery studio for a detailed investigation of 3D interactions. As per the docking result, the Phe-Tyr was found to the be most promising dipeptide lead as a potent inhibitor of CK2 with a ΔG value of -9.06Kcal/mol followed by Phe-His value of ΔG = -8.44 in comparison to standard drug Lenvatinib and Sorafenib whose ΔG value are -8.40 & -9.37 respectively. In SVM results were some differences such as mostly dipeptides that have similar to standard drugs belonging to the Tryptophan family followed by proline and Phenylalanine. In the Gaussian classifier, the good-scoring peptides were Pro-Trp, Trp-Thr, Trp-Ser, and Trp-Ala. When comes to cosine similarity Pro-Ser followed by Pro-Thr, Pro-Leu & Pro-His considered the most promising lead dipeptides. Comparative studies found that there were some differences between man-made results & M.L results.